2012
DOI: 10.1038/ajg.2012.299
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Columnar Lined Esophagus in Gastroesophageal Reflux Disease (GERD) Patients undergoing upper endoscopy

Abstract: If BE is defined by the presence of CLE alone on upper endoscopy, up to 25% of GERD patients are diagnosed with this lesion. Enrolling all these patients in surveillance programs would have significant ramifications on health-care resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 43 publications
1
28
1
Order By: Relevance
“…ordinary risk factors for BE (e.g. male gender, heartburn, hiatal hernia) cannot be applied for BE <1 cm in length [21], a condition that is sometimes associated with the presence of gastric mucosal atrophy and metaplasia [2]. Hence, the risk factors in Asian people for distinct BE with a length >2-3 cm, which is often encountered in Western countries, are largely unknown [22].…”
Section: Introductionmentioning
confidence: 99%
“…ordinary risk factors for BE (e.g. male gender, heartburn, hiatal hernia) cannot be applied for BE <1 cm in length [21], a condition that is sometimes associated with the presence of gastric mucosal atrophy and metaplasia [2]. Hence, the risk factors in Asian people for distinct BE with a length >2-3 cm, which is often encountered in Western countries, are largely unknown [22].…”
Section: Introductionmentioning
confidence: 99%
“…The study reporting the lowest rate of histopathological BE diagnosis was conducted in Spain (0.08%) (48). The highest prevalence of BE was detected in the USA (14.1%) (49).…”
Section: The Epidemiology Of Gerd Complications In Turkey and Around mentioning
confidence: 99%
“…A recent study from the University of Chicago found a 150-fold increased prevalence of BE if goblet cells are not required for this diagnosis. 19 Balasubramanian et al, 20 studied 1058 patients with gastroesophageal reflux disease and found a prevalence of CLE on index endoscopy of 23.3%, whereas CLE with IM was found in only 14.1%. On multivariate analysis, heartburn duration for 45 years, Caucasian race and the presence of a hiatal hernia were found to be independent predictors for CLE, and CLE length was significantly associated with the presence of IM.…”
Section: The Evolving Definition Of Bementioning
confidence: 99%